Ekonomiczne mierniki wzrostu i zmienności - Janaszak, Tadeusz (Economic measures of growth and change, 2005)
In this paper is considered the local property of economic processes. The economic process is said a real function. In the science of economics the shape of the function is global property of economic process. The local property of the processes is an algebraic expression. Each expression contains: the derivative of the function, and alternatively the value of the function, or the value of the argument of the function; it is represented by an tangent line to the process. Local properly of the process is represented by the tangent lines: linear, exponential, power or logarithmic, depending of the aim of the research. Each of this method is a stal ling point to the construction of the calculus. The four methods are equivalent. Each of the method constructs specific language to the diverse problems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 344-355